Ultra-thin ZrO2 overcoating on CuO-ZnO-Al2O3 catalyst by atomic layer deposition for improved catalytic performance of CO2 hydrogenation to dimethyl ether. (4th June 2023) - Fan, Xiao; Jin, Baitang; He, Xiaoqing; Li, Shiguang; Liang, Xinhua
Abstract: An ultra-thin overcoating of zirconium oxide (ZrO2 ) film on CuO-ZnO-Al2 O3 (CZA) catalysts by atomic layer deposition (ALD) was proved to enhance the catalytic performance of CZA/HZSM-5 (H form of Zeolite Socony Mobil-5) bifunctional catalysts for hydrogenation of CO2 to dimethyl ether (DME). Under optimal reaction conditions (i.e. 240 °C and 2.8 MPa), the yield of product DME increased from 17.22% for the bare CZA/HZSM-5 catalysts, to 18.40% for the CZA catalyst after 5 cycles of ZrO2 ALD with HZSM-5 catalyst. All the catalysts modified by ZrO2 ALD displayed significantly improved catalytic stability of hydrogenation of CO2 to DME reaction, compared to that of CZA/HZSM-5 bifunctional catalysts. The loss of DME yield in 100 h of reaction was greatly mitigated from 6.20% (loss of absolute value) to 3.01% for the CZA catalyst with 20 cycles of ZrO2 ALD overcoating. Characterizations including hydrogen temperature programmed reduction, x-ray powder diffraction, and x-ray photoelectron spectroscopy revealed that there was strong interaction between Cu active centers and ZrO2 .